SPIRITUAL LEADERSHIP (SPIRIT IMPLEMENTATION AS LEADERSHIP MODELS IN ISLAMIC EDUCATIONAL INSTITUTIONS) - Siregar, Kardina Engelina; Putra, Ali Musri Semjan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The current situation of Islamic educational institutions is facing a negative cycle and quality problems. This situation is caused by ineffective management at the Islamic Education Institute (LPI). Studies show that leadership is the key to changing negative cycles. He also played a big role in establishing Islamic education. To transform Islamic education into a reference LPI, strong leadership is needed to build quality and superior human resource management. Strong leadership is leadership that has a vision to create effective organizational processes, culture and a good learning environment. Undoubtedly, the leadership model in question is not a conventional leadership model; rather, it is a model of extraordinary leadership—spiritual leadership that brings enlightenment to the world of education. Therefore, leadership based on religious ethics is also called spiritual leadership. Leadership that creates inspiration and innovation.